Development of an Onomatopoeia Learning Support System for Congenital Visually Impaired Individuals Using Haptic Devices - Kano, Toru; Akakura, Takako (Journal of Information Processing, 2025)
Congenital visually impaired individuals especially in Japan, have difficulty understanding some onomatopoeia because Japanese onomatopoeia is often formed from visual information. To solve this problem, in this paper, we developed a system that enables users to experience and understand the movements of objects through a haptic device. As a result of the evaluation experiment, it was suggested that our system could convey the image of onomatopoeia to users only using force feedback. In other words, the results indicate that congenital visually impaired individuals would be able to understand onomatopoeia based on visual information by using our system.